Moral regulation: historical geography and scale - Legg, Stephen; Brown, Michael (Elsevier, 2013)
This paper introduces a special issue on the historical geography of moral regulation and scale. The paper examines the rich and varied work of geographers on moral geographies before looking at wider work on moral regulation influenced by Michel Foucault. Highlighting the significance of the neglected dimension of scale, the paper introduces the themes examined in the subsequent papers.